Nitrite circumvents platelet resistance to nitric oxide in patients with heart failure preserved ejection fraction and chronic atrial fibrillation. Issue 10 (12th April 2018) - Borgognone, Alessandra; Shantsila, Eduard; Worrall, Sophie M; Prompunt, Eakkapote; Loka, Thomas; Loudon, Brodie L; Chimen, Myriam; Ed Rainger, G; Lord, Janet M; Turner, Ashley; Nightingale, Peter; Feelisch, Martin; et al.
Abstract: Aims: Heart failure (HF) is a pro-thrombotic state. Both platelet and vascular responses to nitric oxide (NO) donors are impaired in HF patients with reduced ejection fraction (HFrEF) compared with healthy volunteers (HVs) due to scavenging of NO, and possibly also reduced activity of the principal NO sensor, soluble guanylate cyclase (sGC), limiting the therapeutic potential of NO donors as anti-aggregatory agents. Previous studies have shown that nitrite inhibits platelet activation presumptively after its reduction to NO, but the mechanism(s) involved remain poorly characterized. Our aim was to compare the effects of nitrite on platelet function in HV vs. HF patients with preserved ejection fraction (HFpEF) and chronic atrial fibrillation (HFpEF–AF), vs. patients with chronic AF without HF, and to assess whether these effects occur independent of the interaction with other formed elements of blood. Methods and results: Platelet responses to nitrite and the NO donor sodium nitroprusside (SNP) were compared in age-matched HV controls ( n = 12), HFpEF–AF patients ( n = 29), and chronic AF patients ( n = 8). Anti-aggregatory effects of nitrite in the presence of NO scavengers/sGC inhibitor were determined and vasodilator-stimulated phosphoprotein (VASP) phosphorylation was assessed using western blotting. In HV and chronic AF, both nitrite and SNP inhibited platelet aggregation in a concentration-dependent manner. Inhibition of platelet aggregation by the NO donor SNP was impaired in HFpEF-AF patients compared with healthy and chronic AF individuals, but there was no impairment of the anti-aggregatory effects of nitrite. Nitrite circumvented platelet NO resistance independently of other blood cells by directly activating sGC and phosphorylating VASP. Conclusion: We here show for the first time that HFpEF-AF (but not chronic AF without HF) is associated with marked impairment of platelet NO responses due to sGC dysfunction and nitrite circumvents the 'platelet NO resistance' phenomenon in human HFpEF, at least partly, by acting as a direct sGC activator independent of NO.